Efektifitas dan Orientasi Penggunaan Media Sosial dalam Menanamkan Nilai-Nilai Moderasi Beragama bagi Siswa dalam Mata Pelajaran Pendidikan Agama Islam - Desiska Desiska; Mirzon Daheri (UIN Fatmawati Sukarno Bengkulu, 2024)
This study aims to explain the effectiveness of using social media in instilling religious moderation values for students in Islamic Religious Education (PAI) subjects and identify the most effective orientation of using social media in supporting religious moderation for students in Islamic Religious Education (PAI) subjects at SMP Negeri 03 Tebat Karai, Kepahiang Regency, Bengkulu on academic year 2023-2024. In this study, researchers used a qualitative approach with a type of case study research and descriptive in nature. The design used in this research is a single case design, which is case study research that emphasizes research on only one case unit. The data collection techniques use observation, interviews, and documentation. The results of this study show that social media allows the delivery of religious moderation messages in an interesting and relevant way because they can reach a wide audience and provide various types of content. First, social media can help students obtain educational materials that support moderation, such as articles, lectures and infographics delivered by well-known educators and religious figures. Second, social media sites can allow students to actively interact with the content. Third, religious education with social media allows for more personalized and flexible learning. The most effective orientation for using social media to support religious moderation for students in Islamic Religious Education (PAI) subjects involves an integrated approach focused on delivering moderation messages in a relevant and engaging way. First, this orientation should begin with the selection of social media platforms that match students' preferences and habits that emphasize the principles of tolerance, justice and mutual respect. Second, this orientation involves utilizing the interactive features of social media to encourage students' active engagement. Third, training and guidance for educators in using social media as an educational tool is essential.